PROXIMATE COMPOSITION AND NUTRITIVE VALUE OF LEAFY VEGETABLES CONSUMED IN NORTHERN CÔTE D’IVOIRE - Oulai Patricia; Lessoy Zoue; Rose-Monde Megnanou; Ryta Doue; Sébastien Niamke (European Scientific Journal, ESJ, 2014)
In tropical Africa, leafy vegetables are traditionally cooked and eaten as a relish together with a starchy staple food. Nevertheless, scientific report on their nutritive potential is scanty. In order to contribute to their wider utilization and valorization, leafy vegetables consumed in Northern Côte d’Ivoire (Amaranthus hybridus, Andasonia digitata, Ceiba patendra, Hibiscus sabdariffa and Vigna unguiculata) have focused our attention. The physicochemical and nutritive properties of these leafy vegetables were investigated and the results obtained were as follow: moisture (69.93 - 87.40%), crude proteins (13.12 - 22.26%), crude fibres (12.11 - 33.00%), ash (7.25 - 26.79%), carbohydrates (26.19 - 59.99%), crude lipids (1.17 - 4.90%) and food energy (134.87 - 312.92 kcal/100g). The mineral elements contents were high with remarkable amount of K (848.3 - 3970 mg/100g), Ca (1331.15 - 4680 mg/100g), Mg (345.55 - 2110 mg/100g), P (343.53 - 1320 mg/100g) and Fe (30.71 - 90.00 mg/100g). The Ca/P ratio was desirable and ranged from 2.75 to 9.99. These leafy vegetables also contained appreciable levels of vitamin C (30.00 - 60.01 mg/100g) and polyphenols (134.07 - 294.83 mg/100g). The studied leafy vegetables highlighted antioxidant activity varying from 69.05 to 80.21%. All these results indicate that the studied leafy vegetables if consume in sufficient amount would contribute greatly to the nutritional requirement for human health and to the food security of Ivorian population.